X-ray computed tomography for metals using fourier reconstruction - Mantala C. (2014)
Computed tomography (CT) is one of the most popular methods in non-destructive testing for industrial materials. Although there are many medical-related research activities on CT, there are not many of those for other materials, especially metals. In this paper, we propose an X-ray CT image reconstruction method based on Fourier transform for two kinds of industrial materials, i.e., iron and aluminum. A new interpolation method in Fourier space is proposed to increase the quality of reconstructed images. An offset adjustment in sinograms is also performed prior to the Fourier reconstruction to enhance the focus of reconstructed images. The experimental results show that the Fourier reconstruction with our interpolation method yields good-quality reconstructed images whilst taking much shorter computational time than the popular back projection reconstruction. © 2006 IEEE.